DESIGNING TEACHING MATERIAL OF SIMPLE PAST TENSE USING SHALAWAT SONG FOR HIGH SCHOOL SSTUDENTS - Nurul Aini; Muhammad Saifuddin (Universitas Pesantren Tinggi Darul Ulum Jombang (Unipdu), 2021)
This research was Research Design. It was conducted using three phases of Hanafin and Pecks’ model design. The phases are need assessment, design and implementation. The need assessment was to analyze the students’ need. It was conducted by giving test. Meanwhile, the sampling was taken using cluster random sampling. This research took 21 students from the eighth class. The finding of this research as follows, a) the students mainly had difficulty in answering the test of simple past tense topic, b) some students common errors found in this research were the use of time signal, error in using auxiliary and “to be” past, changing regular and irregular – infinitive verbs to past form and arranging the sentences of verbal and nominal of simple past tense. The results of the students’ needs were used as main point to design the material using sholawat songs. Furthermore, the design phase was to modify the three sholawat song chosen by students from questionnaires given.